Moral Value in The Story of Bangbang Teja in Balamut of Gusti Jamhar Akbar (Sainul Hermawan Transcription) - Noor Indah Wulandari; Heppy Lismayanti (Yogyakarta State University, 2019)
Lamut serves many values the lives of individuals with other individuals in the community, good value education, moral and cultural. Lamut art over the centuries has helped the establishment of the pattern of attitude, mindset, and the behaviour of community supporters. Literary works are able to uplift its readers from the everyday to the level of superficiality is more civilized and subtil, adding to the richness of the inner connoisseur, being more sensitive to life and living. Therefore, the need to do research to learn more about the value of moral in the acts of particularly lamut Bangbang Teja Aria. This research is a kind of qualitative research with literary and sociological approach using the method of dekskriptif analysis, i.e. describing the facts which are then followed by analysis. The data source of this research in the form of translation and transcript book story lamut episode story in the Aria Teja Bangbang balamut Gusti Jamhar Akbar, by Sainul Hermawan. Prints the year 2017 published by Scripta Cendikia Banjarbaru, South Kalimantan. As for the engineering data analsis in this study i.e., descriptive techniques (Arumsari, 2016:20), which lays out the overall data in advance. Next the researchers interpret or identifying data collected. Results of the study of moral values in the story such as Aria Teja Bangbang: 1) Relationship of humans with God includes two aspects: (1) and (2) the grace of God. 2) human relationships with himself include six aspects, namely (1) optimistic; (2) to be honest; (3) the ingenious; (4) soft; (5) liberality; and (6) patient. And 3) human relationships with other human beings in a social sphere covers four aspects: (1) give nasih; (2) friendship; (3) like the meolong; (4) the faithful; (5) willing to help.